Cultivar uma prática de si no contemporâneo : yoga, um êthos - Rabello, Ernesto Grillo (2017)
What are we at the present time? This question, one pole of modern philosophy, is the main engine of this work and is also the driver of its methodology. Nowadays, this question is directed to the relations between contemporary capitalism and its subjectivity production, not only to determine the ways we are producing ourselves through the global market but also for us to perceive ways of resistance to this production: possibilities of existence that escape from capitalistic control and its serializations. This thesis explores these lines: how can we produce ourselves today? Through Michel Foucault"s, Gilles Deleuze"s and Felix Guattari"s works, we intend to analyze the ways we are living in this contemporary capitalism context (knowledge and power axes), as well as we aim to think how can corporal practices become exercises of freedom, producing new relations with political relevance (ethics axis). Therefore, we affirm that the cultivation of a corporal practice can be a way to exercise a life with spaces for autonomy. For this present work, we delineate the yoga practice as the main field of analysis, in a foucaultian genealogic perspective, given the peculiarity of this researcher-practitioner author. We search in Michel Foucault"s work about the technologies of the self some elements that help us in this thinking-exercise, thereby affirming the possibility of the practice of yoga to become the production of an ethos, a way of life. We highlight the relevance of this kind of movement nowadays in the way that Felix Guattari called collective processes of singularization or an incarnation of life for oneself, to what Gilles Deleuze would call the emergency of a new self as a resistance focus. In this thesis we aimed to develop a research that explore critically the occidental thought in its interface with psychology; also a research situated in the contemporary academic context; moreover we intended to develop a research that cares for conceptual rigor and for dedication to opening these concepts for non-academic readers.